Detection of O25b-ST131 clone in extended spectrum beta-lactamase-producing E. coli from urinary tract infections in Mexico - Duran-Bedolla, Josefina; Téllez-Sosa, Juan; González-Villoria, Ana María; Barrios-Camacho, Humberto (The Journal of Infection in Developing Countries, 2024)
Introduction: Escherichia coli has emerged as an important pathogen in urinary tract infections (UTIs) due to the rapid acquisition of antibiotic resistance genes. This enhances the ability of E. coli to colonize and creates therapeutic challenges within the healthcare system. This study aimed to identify the extended spectrum beta-lactamase (ESBL) and O25b-ST131 pandemic clones in E. coli isolated from two hospitals in Mexico. Methodology: Bacterial identification and antibiotic susceptibility tests were conducted using the VITEK 2 system. The ESBL and plasmid-mediated quinolone resistance (PMQR) genes were identified by polymerase chain reaction (PCR). E. coli genotyping was carried out by the phylogenetic group analysis and O25b-ST131 identification. Results: A total of 103 unique E. coli clinical isolates were analyzed from a pool of 1,002 strains; 75% obtained from UTIs and vaginal secretions. Multi-resistant antibiotic profiles were observed. Notably, the presence of the aac(6`)lb-cr and qnr genes was associated with 100% ciprofloxacin resistance, when ESBL was present. Additionally, the B2 phylogenetic group was identified, with 23% of isolates belonging to the O25b-ST131 clone. Conclusions: Our research revealed a 10% prevalence of ESBL, in contrast to global prevalence rates. The resistance profiles suggest that the effectiveness of these commonly used antibiotics in treating E. coli-associated UTIs or vaginal infections has decreased significantly. Excessive use of antimicrobial agents contributes to the regional variation. Our results underscore the importance of monitoring the molecular epidemiology, antibiotic resistance, and transmission dynamics of the O25b-ST131 E. coli clone.